UV SPECTROPHOTOMETRIC METHOD FOR QUANTITATIVE DETERMINATION OF AGOMELATINE IN COATED TABLETS - Fábio de Souza Barbosa; Vanise Coty Rodrigues; Nadia Maria Volpato; Elfrides E. S. Schapoval; Martin Steppe; Cássia V. Garcia; Andreas S. L. Mendez (Drug Analytical Research, 2017)
UV spectrophotometry is an analytical technique used routinely for qualitative and quantitative assay due the low cost and reliability during analysis. In this work, it was validated a quantitative UV method for determination of agomelatine in coated tablets. The parameters specificity, linearity, precision, accuracy and robustness were evaluated according to official guidelines. Methanol was selected as solvent and the maximum wavelength for drug analysis was 230 nm. The purposed assay showed to be specific and the linearity was proved in a range of 0.5 - 2.5 µg/mL. The RSD values obtained during precision assay (inter-day RSD = 1.75%) indicated the method reproducibility, and the accuracy testing showed good results from recovery test. Robustness assay was complementary and showed that the purposed method is adequate for drug quantitation in commercial samples, being a reliable alternative to chromatographic assay.